Risk factors for tuberculosis smear non-conversion in Eden district, Western Cape, South Africa, 2007–2013: a retrospective cohort study. Issue 1 (December 2016) - Mlotshwa, Mandla; Abraham, Natasha; Beery, Moira; Williams, Seymour; Smit, Sandra; Uys, Margot; Reddy, Carl; Medina-Marino, Andrew
Abstract Background Tuberculosis (TB) continues to be a major global health problem. While progress has been made to improve TB cure rates, South Africa's 76 % smear-positive pulmonary TB (PTB) case cure rate remains below the WHO target of 85 %. We report on the trends of TB smear non-conversion and their predictors at the end of an intensive phase of treatment, and how this impacted on treatment outcomes of smear-positive PTB cases in Eden District, Western Cape Province, South Africa. Methods Routinely collected, retrospective data of smear-positive PTB cases from the electronic TB register in Eden District between 2007 and 2013 was extracted. Non-conversion was defined as persistent sputum smear-positive PTB cases at the end of the two or three month intensive phase of treatment. Chi-square test for linear trend and simple linear regression analysis were used to analyse the change in percentages and slope of TB smear non-conversion rates over time. Risk factors for TB non-conversion, and their impact on treatment outcomes, were evaluated using logistic regression models. Results Of 12, 742 total smear-positive PTB cases included in our study, 12.8 % (n = 1627) did not sputum smear convert; 13.3 % (1411 of 10, 574) of new cases and 9.9 % (216 of 2168) of re-treatment cases. Although not statistically significant in either new or re-treatment cases, between 2007 and 2013, smear non-conversion decreased from 16.4 to 12.7 % (slope = −0.60; 95 % CI: −1.49 to 0.29;p = 0.142) in new cases, and from 11.3 to 10.8 % in re-treatment cases (slope = −0.29; 95 % CI: −1.06 to 0.48;p = 0.376). Male gender, HIV co-infection and a >2+ acid fast bacilli (AFB) smear grading at the start of TB treatment were independent risk factors for non-conversion (p < 0.001). Age was a risk factor for non-conversion in new cases, but not for re-treatment cases. Non-conversion was also associated with unsuccessful treatment outcomes (p < 0.01), including treatment default and treatment failure. Conclusions Smear-positive PTB cases, especially men and those with identified risk factors for non-conversion, should be closely monitored throughout their treatment period. The South African TB control program should invest in patient adherence counselling and education to mitigate TB non-conversion risk factors, and to improve conversion and TB cure rates.